Pronominal Morphology in the Anatolian Language Family - Kloekhorst, Alwin (2012)
In the following article, the pronominal morphology from four major ancient Anatolian languages (Hittite, Cuneiform Luwian, Hieroglyphic Luwian and Lycian) will be treated. It will be argued that apart from a few elements of unclear origin, the pronouns in these languages are for the most part built up of morphemes that can be traced back to Proto-Indo-European.
Keywords: Lycian; Luwian; Hittite; Anatolian language family; Tello